Genome‐wide association study of osteochondrosis in the tarsocrural joint of Dutch Warmblood horses identifies susceptibility loci on chromosomes 3 and 10. (25th December 2012) - Orr, N.; Hill, E. W.; Gu, J.; Govindarajan, P.; Conroy, J.; van, E. M.; Ducro, B. J.; van, J. A. M; Knaap, J. H.; van, P. R.; MacHugh, D. E.; Ennis, S.; et al.
Summary Equine osteochondrosis is a developmental joint disease that is a significant source of morbidity affecting multiple breeds of horse. The genetic variants underlying osteochondrosis susceptibility have not been established. Here, we describe the results of a genome‐wide association study of osteochondrosis using 90 cases and 111 controls from a population of Dutch Warmblood horses. We report putative associations between osteochondrosis and loci on chromosome 3 (BIEC2‐808543; P = 5.03 × 10−7) and chromosome 10 (BIEC2‐121323; P = 2.62 × 10−7).